Associations of Pain Vigilance and Past and Current Pain with Kinesiophobia after Sport Injury in Current and Former Athletes from Iran and the United States - Fahimeh Badiei; Britton W. Brewer; Judy L. Van Raalte (Journal of Functional Morphology and Kinesiology, 2023)
High levels of kinesiophobia (fear of movement/reinjury) have been related to reinjury and adverse injury rehabilitation outcomes in athletes. To examine the extent to which pain vigilance, memory of injury-related pain, and current injury-related pain were associated with kinesiophobia, a cross-sectional study was conducted with 172 current and former athletes from Iran (n = 113) and the United States (n = 59) who reported having experienced a serious injury that affected their participation or performance in sport. Questionnaires were administered to participants via an online survey platform. Hierarchical multiple regression analysis revealed that pain vigilance and memory of pain were positively associated with kinesiophobia, with the full model accounting for 31% of the variance in kinesiophobia scores. The findings suggest that excessive attention to pain-related stimuli and memory of pain for an injury that occurred an average of four years earlier may contribute to the experience of fear of movement and reinjury in current and former athletes.